Marii Nagajowej „wiedza o człowieku”, czyli o charakterystyce i charakteryzowaniu - Grzegórzek, Mirosław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Maria Nagajowa’s works in the field of methodics of the linguistic efficiency cultivation and exercises in speaking and writing is especially important for the Polish language teaching practice. The author created an alphabet of the Polish language teaching metodics: the detailed and pattern-creating description of didactic procedures concerning statement genres at school. Among them, the concept of “the knowledge about a man” inscribed in the work on figure’s characteristics, deserves special emphasis. The article is an attempt to synthesize the author’s views connected with the “analysis of a human” in Polish lessons. In Nagajowa’s conception characterizing the figure becomes the process and the characteristics escalates to the rank of department on the Polish language teaching, entitled b the author as “The Knowledge about a Human”.
Keywords: figure’s characteristics; characterizing; text-creating competence; Maria Nagajowa